ANALISIS INTEGRASI NILAI-NILAI PENDIDIKAN ISLAM DENGAN NILAI-NILAI BUDAYA JAWA DALAM NOVEL WIGATI KARYA KHILMA ANIS - Shilvy Naily Inayah; Nurotun Mumtahanah; Ahmad Hanif Fahruddin; Siti Suwaibatul Aslamiyah (Akademika, 2022)
Islam and Javanese culture have a close relationship, which has now begun to disappear both due to the progress of the times and the sophistication of technology. The purpose of this research is to find out the values of Islamic education contained in the novel Wigati by Khilma Anis, to find out the values of Javanese Culture in the novel Wigati by Khilma Anis, and to find out the integration of the value of Islamic education with the value of Javanese Culture in the novel Wigati by Khilma Anis. The researcher used a descriptive qualitative research by presenting data descriptively through documentation techniques. The subject of this study is the novel Wigati. The results of this study show that, the Islamic educational values contained in the wigati novel are tauhid, worship, moral and social values, the Javanese cultural values contained in the Wigati novel are the values of tradition and belief, while the integration of Islamic educational values with Javanese cultural values in wigati novels includes integration between the value of tawhid and the value of tradition (wayang), the value of tauhid with the value of belif in talismans, the value of tauhid which concerns destiny/qadha’ and qadar Allah with Javanese cultural values in the form of belief values in rituals before making keris/ heirloom objects by choosing good days, and social values with Javanese cultural values in the form of ritual offerings/ selametan.